2010
DOI: 10.3109/17483100903437633
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb neurorehabilitation in patients with stroke using haptic device system: Reciprocal bi-articular muscle activities reflect as a result of improved circle-drawing smoothness

Abstract: Patients with stroke could achieve smooth motor performance with the restoration of the reciprocal EMG activities in biarticular arm muscles. Therefore, the reciprocal EMG activities in biarticular arm muscles in response to circle drawing would be an index for the progressive improvements of smooth motor functions in the upper limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Furthermore, even in clinical practice, especially to assess the patients with motor function disorder, the working distance and movement pattern is studied to observe the improvement of motor function recovery. The inspection procedure not only considers one aspect or point of view but the standard protocol of the evaluation also considers multidimensional aspects such as the progress of the motor function recovery, the mechanism of recovery, the body change to the paralyzed side of the patients and other aspects related to the patient's condition which are quantitatively analyzed [20]- [22]. Therefore, the evaluation method of the sanding movement training assessed in our novel measurement system suggests that obtaining motion distance and motion speed, which objectively evaluate the exercise capacity and the range of motion during the training session is effective.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even in clinical practice, especially to assess the patients with motor function disorder, the working distance and movement pattern is studied to observe the improvement of motor function recovery. The inspection procedure not only considers one aspect or point of view but the standard protocol of the evaluation also considers multidimensional aspects such as the progress of the motor function recovery, the mechanism of recovery, the body change to the paralyzed side of the patients and other aspects related to the patient's condition which are quantitatively analyzed [20]- [22]. Therefore, the evaluation method of the sanding movement training assessed in our novel measurement system suggests that obtaining motion distance and motion speed, which objectively evaluate the exercise capacity and the range of motion during the training session is effective.…”
Section: Discussionmentioning
confidence: 99%
“…Applications range from training in dental techniques1 and laparoscopic surgery2 to the rehabilitation of patients with cerebral palsy or stroke with functionally impaired upper or lower limbs 3 4. Recently, a group in Illinois, USA reported that they had used haptic technology successfully to assess the variation in surgical proficiency among orthopaedic residency trainees 5.…”
Section: Haptic Technologymentioning
confidence: 99%
“…Virtual reality environments and games have been developed and combined with Rehab robots to facilitate long-term training and increase movement in therapy [16,17]. Miyoshi et al (2010) pointed out that drawing a circle requires complex movements and the coordination of multiple muscular co-contractions as well as eccentric activity [18] in the medial/lateral and forward/ backward directions. Ju et al (2005) used a robot to guide the upper limbs of subjects in linear and circular movements [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ju et al (2005) used a robot to guide the upper limbs of subjects in linear and circular movements [19]. Based on previous works [18,19], the complex circle-drawing movement should enhance the coordination and motoring of shoulder flexion/extension. Motions that mimic circle drawing in the vertical plane are common in daily life, such as turning a steering wheel or cleaning windows.…”
Section: Introductionmentioning
confidence: 99%